Sex-Differences in the Oxygenation Levels of Intercostal and Vastus Lateralis Muscles During Incremental Exercise - Espinosa-Ramírez, Maximiliano; Moya-Gallardo, Eduardo; Araya-Román, Felipe; Riquelme-Sánchez, Santiago; Rodriguez-García, Guido; Reid, W. Darlene; Viscor, Ginés; Araneda, Oscar F.; Gabrielli, Luigi; Contreras-Briceño, Felipe (Frontiers in Physiology, 2021)
This study aimed to examine sex differences in oxygen saturation in respiratory (SmO2-m.intercostales) and locomotor muscles (SmO2-m.vastus lateralis) while performing physical exercise. Twenty-five (12 women) healthy and physically active participants were evaluated during an incremental test with a cycle ergometer, while ventilatory variables [lung ventilation (V.E), tidal volume (Vt), and respiratory rate (RR)] were acquired through the breath-by-breath method. SmO2 was acquired using the MOXY® devices on the m.intercostales and m.vastus lateralis. A two-way ANOVA (sex × time) indicated that women showed a greater significant decrease of SmO2-m.intercostales, and men showed a greater significant decrease of SmO2-m.vastus lateralis. Additionally, women reached a higher level of ΔSmO2-m.intercostales normalized to V.E (L⋅min–1) (p < 0.001), whereas men had a higher level of ΔSmO2-m.vastus lateralis normalized to peak workload-to-weight (watts⋅kg–1, PtW) (p = 0.049), as confirmed by Student’s t-test. During an incremental physical exercise, women experienced a greater cost of breathing, reflected by greater deoxygenation of the respiratory muscles, whereas men had a higher peripheral load, indicated by greater deoxygenation of the locomotor muscles.